Influence of frugivore activity on the species abundance of seedlings and saplings in a lowland tropical forest in Colombia (2015)
Although seed dispersal plays a critical role for plant regeneration, the long-term benefits of frugivores for recruitment success have been poorly explored. We evaluated the relative importance of tree species abundance and of frugivore-related factors for successful plant recruitment on 18 tree species in a lowland Colombian rain forest. We combined census data from four 1-ha plots of trees (>10 cm dbh), saplings (1-5 cm dbh) and seedlings ( less than 1.7 m) with a dataset describing tree-frugivore interactions. Seedling abundance was higher for large-seeded species dispersed by the spider monkey, while sapling abundance was higher for large-seeded species dispersed by birds. The identity of the dispersal agent and its interaction with seed size explained 20-30% of the total variance in seedling and sapling abundance across scales. Seed size consistently influenced the species abundance of seedlings and saplings across scales, but in opposite ways. These developmental changes suggest that what is beneficial to seedlings is not necessarily beneficial to saplings. Species identity explained 10-50% of the total variance in seedling and sapling abundance among and within 1-ha plots. Overall, our findings suggest that recruitment success is context-dependent as the relative importance of the different variables addressed may shift along spatial and temporal scales. © Cambridge University Press 2015.